A compact low loss high isolation DC-45GHz SPST switch in 0.13-μm CMOS process. (October 2018) - Deng, Chun; Yang, Hong-Qiang; Gong, Min
Abstract: A compact low loss high isolation wideband single-pole-single-throw (SPST) switch that operates from DC to 45 GHz is analyzed and implemented in 0.13-μm CMOS process. Based on series-shunt topology and traveling-wave concept, the SPST switch achieves broadband characteristics. With circuit analysis and optimization, the switch exhibits insertion loss lower than 3 dB, isolation higher than 47 dB and return loss below −13 dB from DC to 45 GHz. The input 1-dB compression point is 10dBm with a 1.5 V control voltage. The SPST switch has a compact core area of 350  μm × 80  μm.